Objects of belonging and displacement; Artefacts and European migrants from colonial Indonesia in colonial and post-colonial times - Drieënhuizen, Caroline (UI Scholars Hub, 2022)
As colonial Indonesia never was intended to be a “settler colony”, many Dutch citizens spent only a certain period of their lives there before returning to the Netherlands. However, there were also Europeans, many with Asian-European roots, who had called the colony home for generations and were forced to leave that home after 1945. All these different types of colonial migrants were displaced and maintained, built and reinforced their relations with the country (whether it was the colony or the “motherland”) they had left. This transnationalism (or, as I argue here, imperial orientation) took shape not only legally or relationally but also experientially (D. Ip, C. Inglis, and C.T. Wu 1997). In this article I show how, in both the colonial and post-colonial periods, objects helped European colonial migrants establish and maintain social relationships. Objects shaped identities and people’s status; bolstering increase migrants’ sense of “a continuous transnational self and identity”, a feeling of home, but also feelings of displacement.